Gaya Belajar Gen Alpha di Era Digital - Ronny Gunawan; Maya Zaina Billah; Rosiani Silalahi; Henrik Tuka (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research examines the learning styles of the alpha generation in the digital era, the alpha generation is a generation consisting of children and born after 2010, the alpha generation is very close to the world of technology and digital, they grow and develop with digital devices such as smartphones and computers. This research aims to find out the learning style of the alpha generation, including their tendency in online learning media, digital learning methods, as well as the importance of the role of parents and teachers in guiding the wise use of technology. The results of this study show that Generation Alpha tends to be interactive towards technology-related learning media and methods such as animation, audio media, educational games, learning apps, and virtual reality (VR). They are very responsive to digital information that is presented visually and auditory that is interesting and easily accessible. The research also found that the role of teachers and parents is very important in guiding and directing the Alpha generation in utilizing technology optimally, so that they can develop their ability to obtain information, use technology, and balanced social-emotional skills.